Combinatory Effect of Nitroxoline and Gentamicin in the Control of Uropathogenic Enterococci Infections - Davorka Repac Antić; Bruno Kovač; Marko Kolenc; Irena Brčić Karačonji; Ivana Gobin; Mirna Petković Didović (MDPI AG, 2024)
Enterococcus faecalis, responsible for a majority of human and nosocomial enterococcal infections, is intrinsically resistant to aminoglycoside antibiotics (such as gentamicin, GEN), which must be used in a combined therapy to be effective. Nitroxoline (NTX) is an old antibiotic, underused for decades, but rediscovered now in an era of growing antibiotic resistance. In this in vitro study, the types of interactions between NTX and GEN on 29 E. faecalis strains were analyzed with an aim to find synergistic antimicrobial and antiadhesion combinations. Transmission electron microscopy (TEM) and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) were used to analyze changes in cell morphology and bacterial proteome after monotreatments and combined treatments. The results showed the synergistic effect for six combinations on eight strains, including the ATCC29212, and an additive effect for most strains. Combinations causing a complete inhibition of adhesion were established. Cell membrane integrity was affected by NTX, while combined NTX/GEN treatment caused dramatic changes in cell morphology. Upregulation of the expression of many proteins was established, with some emerging only after combined treatment. The results strongly imply that NTX has the potential for use in combined therapy with GEN against enterococci and it could further provide a substantial contribution to an ongoing fight against antimicrobial resistance and nosocomial infections.